Enhanced Aqueous Zinc-Ion Batteries Using 3D MoS2/Conductive Polymer Composite - Tongxin Jiang; Sijie Li; Zexiang Luo; Xue Li; Lifeng Zhang; Haisheng San; Xin Li; Yifei Ma (Energies)
MoS2, a typical transition metal dichalcogenide, features a layered structure, multi-phase transition, and tunable band gap, which is a promising candidate for aqueous zinc-ion batteries (AZIBs). Recent studies have focused on the metastable 1T-MoS2 phase, which exhibits superior electrical conductivity and electrochemical activity compared to the more stable 2H phase. Herein, a straightforward one-step hydrothermal method was used to synthesize three-dimensional MoS2/polymer composites (H-MoS2-PEDOT). Under acidic conditions, the polymerization and intercalation of EDOT molecules in the MoS2 layers promote the phase transition from 2H to 1T, thereby enhancing its conductivity and electrochemical performance. Additionally, it was found that the intercalated PEDOT and small amounts of water molecules have contributed to enhancing Zn2+ ion diffusion and cycle stability. As a result, AZIBs based on the H-MoS2-PEDOT composite deliver a high specific capacity of 173.6 mAh g−1 at 1 A g−1, maintaining a specific capacity of 116 mAh g−1 and a capacity retention of 82.8% after 1000 cycles at 5 A g−1.